Pengaruh Kompetensi, Pelatihan Kerja, Komitmen Kerja Terhadap Kinerja Pelaku Usaha Industri Kecil Dan Menengah Binaan Klinik Kemasan Dinas Perindustrian Dan Perdagangan Provinsi Kepulauan Riau Dengan Motivasi Sebagai Variabel Intervening - Afriza, Sari; Satriawan, Bambang; Gunawan, Dahlan (Program Studi Manajemen FEBM UMRAH, 2025)
Small and Medium Industries (SMEs) face various challenges and opportunities that require competency strengthening. The competency issues of Small and Medium Industries (SMEs) in the Riau Islands Province include various challenges that hinder the growth and sustainability of their businesses. The research hypothesis testing was conducted using the Structural Equation Model (SEM) approach. Based on the results of the analysis is Competence, commitment have a significant effect on the motivation of Business Actors Fostered by the Packaging, Training does not have a significant effect on the motivation of Business Actors Fostered by the Riau Islands Province Industry and Trade Office. Work commitment has a significant effect on the motivation of Business Actors Fostered by the Riau Islands Province Industry and Trade Office. Competence, commitment and training have a significant effect on the performance of Business Actors Fostered by the Riau Islands Province Industry and Trade Office. Competence has a significant effect on performance through motivation of Business Actors Fostered by the Riau Islands Province Industry and Trade Office. Training does not have a significant effect on performance through motivation of Business Actors Fostered by the Riau Islands Province Industry and Trade Office.